Government involvement in academic research: Nazarbayev University case study (Journal of Educational Sciences, 2021)
This research is a case study of government involvement in academic research. In the case study, we analyzed what factors influence government involvement in academic research. Specifically, we scrutinized different factors such as language, citizenship, networking, age, and gender that could, to some extent, facilitate or complicate research cooperation between academia and government bodies.Though there are other universities with foreign professors, including KIMEP, SDU, KBTU, the num- ber of foreigners in those universities is insignificant in comparison with NU, and the location of NU provides better access than others.We conducted an online survey among NU faculty, as well as several face-to-face interviews. The survey involved 47 respondents. The findings revealed that the most significant factors influencing gov- ernment involvement in academic research are lack of proficiency in Russian and Kazakh, networking. The implications of this research suggest it is essential to establish particular intermediary institutions between academics and the government in order to facilitate the cooperation and omit unnecessary bureaucratic processes.Key words: academic research; Nazarbayev University faculty; government involvement; Kazakh- stan; case study.